(3GdCSS GdfaSjI dHfGA GdgOa aj GdeLGd GdQjGVjs - (3QGJH GSGeI ceGds ((3GdbGgQIs (3OGQ GdacQ GdYQHjs, 1994)
(3JbOe gPg GdOQGSI fehPLG TGedG eJcGedG ddEJLGgGJ GdfaSjI GdgGeI GdJj jLH eQGYJgG YfO HfGA GdCgOGa aj GdHQfGeL GdQjGVj , GdCeQ GdPj jWhQ GdCOGA GdQjGVj h jfej GdLhGfH GdTNUjI ddQjGVj h Pdc ef NdGd YQV JaUjdj dcGaI GdCSGdjH GdfaSjI GdeJHYI aj HfGA GdgOa aj GdLGd GdQjGVjs
Keywords: (3Yde GdfaS GdQjGVjs